Pemanfaatan Limbah Dedaunan Kering Sebagai Sumber Pendapatan Pasca Bencana Siklon Seroja Pada Rumah Tangga Di Koordinator Wilayah V Jemaat GMIT Nazaret Oesapa Timur, Kelurahan Oesapa - Damaris Y. Koli; Jems Arison Zacharias; Joni Kanisius Olin (Universitas 45 Surabaya, 2023)
After the Seroja cyclone has left, there are lot of garbage scattered in the households of the East Oesapa of Nazareth Congregations. The waste has exceeded the capacity limit on the relatively narrow area of the congregation's house in the East Oesapa area. The abundance of this waste, especially organic waste such as dry leaves, can be used by residents as one of the main ingredients for making compost that has economic value. The purpose of this program is to educate the youth in the Regional Coordinator V, East Oesapa of Nazareth Congregations, in utilizing dry leaf waste into compost as a source of income after the Seroja cyclone. Through this activity, the youth are expected to have the skills to utilize local materials in the vicinity that have economic value and are environmentally friendly. In addition, the youth are also expected to have the knowledge and skills in management of the compost production as a source of income. This program began with a discussion with the youth group of the Regional Coordinator V of the GMIT Nazaret Oesapa Timur congregation as partners about the implementation plan of the community service program. After the plan is completed, the training will be held with materials in the form of using dry leaves as a product with economic value and aspects of business management. The next activity is the practice of making compost products directly involving all participants from the V Korwil youth group, East Oesapa Nazaret Congregation.